Application of quantitative fluorescent polymerase chain reaction analysis for the rapid confirmation of trisomy 13 of maternal origin in a pregnancy with fetal holoprosencephaly, cyclopia, polydactyly, omphalocele and cell culture failure - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Shin-Yin Huang; Wayseen Wang (Elsevier, 2022)
Objective: We present the application of quantitative fluorescent polymerase chain reaction (QF-PCR) for the rapid confirmation of trisomy 13 of maternal origin in a pregnancy with fetal holoprosencephaly (HPE), cyclopia, polydactyly, omphalocele and cell culture failure. Case report: A 21-year-old, gravida 2, para 0, woman was referred for termination of the pregnancy at 17 weeks of gestation because of the abnormal ultrasound finding of alobar HPE. The pregnancy was subsequently terminated, and a 118-g malformed male fetus was delivered with cyclopia, bilateral postaxial polydactyly of the hands and ruptured omphalocele. Postmortem cell culture of the placental tissue and umbilical cord was not successful. The parental karyotypes were normal. QF-PCR analysis using the polymorphic DNA markers of D13S1810, D13S790 and D13S251 on the DNA extracted from placenta, umbilical cord and parental bloods showed trisomy 13 of maternal origin. Conclusion: Perinatal diagnosis of concomitant HPE, polydactyly and omphalocele should raise a suspicion of fetal trisomy 13. QF-PCR analysis is useful for rapid confirmation of trisomy 13 and the parental origin especially under the circumstance of cell culture failure, and the information acquired is very useful for genetic counseling of the parents.